Perception of premature infants' mothers on home visits before and after hospital discharge - Luana Cristine dos Santos; Talita Balaminut; Sarah Nancy Deggau Hegeto de Souza; Edilaine Giovanini Rossetto (Universidad de Antioquia, 2014)
Objective. To understand the meaning of home visits by neonatal nurses for mothers of premature babies. Methodology. A qualitative study was conducted with 21 mothers of families participating in a project that supported families of premature infants, born at a university hospital in the city of Londrina, Brazil. Data collection was conducted through semi-structured individual interviews, using a form with the identification data of mothers and an interview script. Results. Three themes were revealed: the home visit as a support to the family, individualized home care, feeling cared for and supported in performing the baby's care. Conclusion. The home visit from the perspective of longitudinal care was a powerful resource that promoted the link between families and nurses, decreasing doubts, fears and anxieties of the mother. In addition, home care was provided and adherence to care and treatment was encouraged.